(untitled) (Ictus, 2020)
Trousseau syndrome is characterized by the presence of venous or arterial thrombotic events associated with a patient with visceral cancer. We present the case of a 43-year-old woman previously healthy, who presented a clinical picture of systemic embolisms with fever and who developed multiple strokes with embolic features. The progression and multiple-event symptoms with fever and multiple use of antibiotics raised the suspicion of bacterial endocarditis as the first possibility. She was admitted to hospital due to recurrence of ischemic stroke despite aspirin treatment, for diagnosis and treatment. The presence of non-bacterial endocarditis associated with ovarian carcinoma was confirmed, making the diagnosis of Trousseau syndrome feasible. The patient’s hospital evolution was torpid, presenting cerebral hemorrhage associated with anticoagulants, systemic complications, and finally death of the patient 61 days after the first symptom.